Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Methodology for the systematic investigation of the hygrothermal-mechanical behavior of a structural epoxy adhesive - Sander, Sascha; Meschut, Gerson; Kroll, U.; Matzenmiller, A. (International Journal of Adhesion and Adhesives)

On methods to reduce spurious currents within VOF solver frameworks. Part 1: a review of the static bubble/droplet - Inguva, Venkatesh; Schulz, Andreas; Kenig, Eugeny (Chemical Product and Process Modeling)
Abstract In two-phase flows in which the Capillary number is low, errors in the computation of the surface tension force at the interface cause Front-Capturing methods such as Volume of Fluid (VOF) and Level-Set (LS) to develop interfacial spurious currents. To better solve low Capillary number flows, special treatment is required to reduce such spurious currents. Smoothing the phase indicator field to more accurately compute the curvature or adding interfacial artificial viscosity are techniques that can treat this problem. This study explores OpenFOAM, Fluent and StarCCM+ VOF solvers for the classical case of a static bubble/droplet immersed in a continuous aqueous phase, with the focus on the ability of these solvers to adequately reduce spurious currents. The results are expected to be helpful for practicing chemical engineers who use multiphase CFD solvers in their work.

Modelling and simulation of zero-gravity distillation units with metal foams - Wende, Marc; Staggenborg, Christoph; Kenig, Eugeny Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Model Based and Experimental Analysis of the Dynamic Reactive Absorption Loop Behavior - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Proceedings of the 12th international conference Distillation & Absorption 2022)

Modeling Concepts for Reactive Separations - Kenig, Eugeny Y. (Process Intensification by Reactive and Membrane-assisted Separations)

Experimental Analysis of Residual Stresses in CFRPs through Hole-Drilling Method: The Role of Stacking Sequence, Thickness, and Defects - Wu, Tao; Kruse, Roland; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Lauhoff, Christian; Niendorf, Thomas (Journal of Composites Science)
Carbon fiber reinforced plastics (CFRPs) gained high interest in industrial applications because of their excellent strength and low specific weight. The stacking sequence of the unidirectional plies forming a CFRP laminate, and their thicknesses, primarily determine the mechanical performance. However, during manufacturing, defects, e.g., pores and residual stresses, are induced, both affecting the mechanical properties. The objective of the present work is to accurately measure residual stresses in CFRPs as well as to investigate the effects of stacking sequence, overall laminate thickness, and the presence of pores on the residual stress state. Residual stresses were measured through the incremental hole-drilling method (HDM). Adequate procedures have been applied to evaluate the residual stresses for orthotropic materials, including calculating the calibration coefficients through finite element analysis (FEA) based on stacking sequence, laminate thickness and mechanical properties. Using optical microscopy (OM) and computed tomography (CT), profound insights into the cross-sectional and three-dimensional microstructure, e.g., location and shape of process-induced pores, were obtained. This microstructural information allowed for a comprehensive understanding of the experimentally determined strain and stress results, particularly at the transition zone between the individual plies. The effect of pores on residual stresses was investigated by considering pores to calculate the calibration coefficients at a depth of 0.06 mm to 0.12 mm in the model and utilizing these results for residual stress evaluation. A maximum difference of 46% in stress between defect-free and porous material sample conditions was observed at a hole depth of 0.65 mm. The significance of employing correctly calculated coefficients for the residual stress evaluation is highlighted by mechanical validation tests.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

Characterization of residual stresses in fiber metal laminate interfaces - A combined approach applying hole-drilling method and energy-dispersive X-ray diffraction - Wu, T.; Degener, S.; Tinkloh, Steffen Rainer; Liehr, A.; Zinn, W.; Nobre, J.P.; Tröster, Thomas; Niendorf, T. (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Modeling of a hybrid process combining zero-gravity distillation and vapor permeation - Wende, Marc; Kenig, Eugeny Y. (Proceedings Int. Conf. „Distillation and Absorption 2022”)

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Service strength analysis method for adhesively bonded hybrid structures under multiaxial loading - Tittmann, Karsten; Koch, Ilja; Çavdar, Serkan; Gude, Maik; Meschut, Gerson (Proceedings of the 20th European Conference on Composite Materials)
Semi-structural adhesive joints with hyperelastic polyurethane adhesives and large adhesive layer thicknesses enable the realization of innovative hybrid lightweight designs with fiber reinforced plastic (FRP) composites. The design of these adhesively bonded joints with complex mechanical behavior requires a valid and efficient method for computational service life prediction. In this paper, a submodel-based service strength analysis method for adhesively bonded hybrid structures is presented and validated on sub component fatigue tests. The submodel strategy is generalized by periodic boundary conditions to evaluate failure relevant stresses and thus fatigue life in advance and independently from the global structure analysis.

Influence of the Surrounding Sheet Geometry on a Clinched Joint - Martin, Sven; Kurtusic, Kristijan; Tröster, Thomas (Key Engineering Materials)

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, René; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, Sören Antonius; Kenig, Eugeny (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Modelling film and rivulet flows on microstructured surfaces using CFD methods - Bertling, R.; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, S.; Kenig, E.Y. (Chemical Engineering Science)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Numerical Simulation of Solids Conveying in Grooved Feed Sections of Single Screw Extruders - Brüning, Florian; Schöppner, Volker (Polymers 14)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Schöppner, Volker; Gevers, Karina; Tornede, A.; Wever, M.; Hüllermeier, E. (Welding in the World)

Material-specific prediction of the optimal joinig parameters for the screw blind rivet joining process - Moritzer, Elmar; Held, Christian; Hillemeyer, J. (Welding in the World)

Coupled microscopic and micromagnetic depth-specific analysis of plastic deformation and phase transformation of metastable austenitic steel AISI 304L by flow forming - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents the characterization of the microstructure evolution during flow forming of austenitic stainless steel AISI 304L. Due to plastic deformation of metastable austenitic steel, phase transformation from γ-austenite into α’-martensite occurs. This is initiated by the formation of shear bands as product of the external stresses. By means of coupled microscopic and micromagnetic investigations, a characterization of the microstructure was carried out. In particular, this study shows the distribution of the strain-induced α’-martensite and its influence on material properties like hardness at different depths. The microstructural analyses by means of electron backscattered diffraction (EBSD) technique, evidence a higher amount of α’-martensite (ca. 23 %) close to the outer specimen surface, where the plastic deformation and the direct contact with the forming tool take place. In the middle area (ca. 1.5 mm depth from the outer surface), the portion of transformed α’-martensite drops to 7 % and in the inner surface to 2 %. These results are well correlated with microhardness and micromagnetic measurements at different depths. EBSD and atomic force microscopy (AFM) were used to make a detailed characterization of the topography and degree of deformation of the shear bands. Likewise, the mechanisms of nucleation of α’-martensite were discussed. This research contributes to the development of micromagnetic sensors to monitor the evolution of properties during flow forming. This makes them more suitable for closed-loop property control, which offers possibilities for an application-oriented and more efficient production.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Innovative Online Measurement and Modelling Approach for Property-Controlled Flow Forming Processes - Kersting, Lukas; Arian, Bahman; Vasquez, Julian Rozo; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Key Engineering Materials)
The production of complex multi-functional, high-strength parts is becoming increasingly important in the industry. Especially with small batch size, the incremental flow forming processes can be advantageous. The production of parts with complex geometry and locally graded material properties currently depicts a great challenge in the flow forming process. At this point, the usage of closed-loop control for the shape and properties could be a feasible new solution. The overall aim in this project is to establish an intelligent closed-loop control system for the wall thickness as well as the α’-martensite content of AISI 304L-workpieces in a flow forming process. To reach this goal, a novel sensor concept for online measurements of the wall thickness reduction and the martensite content during forming process is proposed. It includes the setup of a modified flow forming machine and the integration of the sensor system in the machine control. Additionally, a simulation model for the flow forming process is presented which describes the forming process with regard to the plastic workpiece deformation, the induced α’-martensite fraction, and the sensor behavior. This model was used for designing a closed-loop process control of the wall thickness reduction that was subsequently realized at the real plant including online measured feedback from the sensor system.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science